2018
DOI: 10.1097/md.0000000000012640
|View full text |Cite
|
Sign up to set email alerts
|

An electrical scalpel conization versus Shimodaira-Taniguchi conization procedure for cervical intraepithelial neoplasia

Abstract: The incidence of cervical intraepithelial neoplasia(CIN) among reproductive-aged women has increased in Japan. Cervical conization is commonly applied for local cervical treatment to preserve fertility. The Shimodaira-Taniguchi (S-T) conization procedure is widely used in Japan. S-T conization uses a high-frequency current and a triangular probe with a linear excision electrode to remove cervical tissue as a single informative specimen. However, alternative of an electrosurgical scalpel (ES) has the advantage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 24 publications
(23 reference statements)
0
9
0
Order By: Relevance
“…A meta-analysis of 35,109 patients with any grade CIN or invasive cancer found that 23% had positive surgical margins 22 . The rate of positive surgical margin involvement in the LEEP varied from 22% to 33.8%, in CKC from 13% to 22.3%, and in ESC from 4.7% to 25.7% 10,21,23–25 . It has been confirmed that a conization depth less than 10 mm might be a risk factor that predicts endocervical resection margins and had the highest sensitivity (100%) among the other factors including cone volume and cone base surface 26,27 .…”
Section: Discussionmentioning
confidence: 98%
“…A meta-analysis of 35,109 patients with any grade CIN or invasive cancer found that 23% had positive surgical margins 22 . The rate of positive surgical margin involvement in the LEEP varied from 22% to 33.8%, in CKC from 13% to 22.3%, and in ESC from 4.7% to 25.7% 10,21,23–25 . It has been confirmed that a conization depth less than 10 mm might be a risk factor that predicts endocervical resection margins and had the highest sensitivity (100%) among the other factors including cone volume and cone base surface 26,27 .…”
Section: Discussionmentioning
confidence: 98%
“…An electronic knife coagulates small blood vessel simultaneously when incising. 13 With less bleeding during incising, a clear surgical field can be maintained, which in turn facilitates a precise incision, and consequently, less bleeding. Second, the purposeful manipulation of the cervix and the change in the cone shape may also be important factors.…”
Section: Discussionmentioning
confidence: 99%
“…5,22 Kigure et al reported that more conservative conization, such as shallow coin-shaped conization, could achieve favorable obstetric outcomes. 13 A smaller amount of the cervical stroma was excised with our modified method, which may be a better alternative in young patients with the desire of future fertility. A thermal artifact remains the main concern of the LEEP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This meta-analysis suggested that prophylactic transvaginal cerclage following conization increases the risk of preterm birth and PROM. In France, a historyindicated cerclage is not recommended for women with only a history of conization [37]. In another study, Kaye and Giraldo-Isaza considered that the increasing risk of PROM following cervical cerclage may related to the risk of ascending infection [38,39].…”
Section: Discussionmentioning
confidence: 99%